1988
DOI: 10.1128/aem.54.7.1756-1760.1988
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of chemical dosing methods for isolating nontuberculous mycobacteria from water supplies of dialysis centers

Abstract: Investigations of nontuberculous mycobacterium (NTM) infections associated with various environmental sources have been hampered by the lack of adequate techniques for selective isolation of these organisms from environmental fluids. This study compared chemical dosing techniques for recovery of NTM from water samples collected from 115 randomly selected dialysis centers. Cell suspensions of NTM group II and IV isolates and gram-negative bacteria were exposed to solutions containing sodium hypochlorite (0.2 ,u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Carson et al . found that 55% of incoming city water in hemodialysis centers throughout the USA contained rapidly growing mycobacteria . Thus, it seems logical that NTM infections are acquired by environmental exposure rather than by person‐to‐person spread as in tuberculous infections.…”
Section: Resultsmentioning
confidence: 99%
“…Carson et al . found that 55% of incoming city water in hemodialysis centers throughout the USA contained rapidly growing mycobacteria . Thus, it seems logical that NTM infections are acquired by environmental exposure rather than by person‐to‐person spread as in tuberculous infections.…”
Section: Resultsmentioning
confidence: 99%
“…One study by Carson et al. showed that these species of RGM are commonly seen in municipal tap water (1), but a broad survey of the existence of RGM in the Japanese environment has not been reported. Our patient's house contained a well and she used the water from it for laundering.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, some other species, e.g. rapidly growing mycobacteria, may be reduced 100-fold by 1.25% oxalic acid in only 10 rnin (Carson et al 1988). Only scant information is available on the survival of mycobacteria after H,S04 treatment.…”
Section: Discussionmentioning
confidence: 99%